Energy harvesting for UWB IIoT devices - Ševčík, Jan; Juráň, Radovan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2025)
This paper focuses on the study and selection of suitable energy harvesting methods, considering specific application scenarios. It includes a comparison of various methods to identify the most optimal solutions and adjustments for efficient energy collection. Finally, the paper presents the design and development of a custom printed circuit board (PCB) featuring a chip that supports ultra-wideband (UWB) technology in accordance with the 802.15.4z standard. The system is powered by a battery, which extends its lifespan and ensures prolonged operation when the harvested environmental energy is sufficient.
Keywords: UWB; Energy Harvesting; DWM3001; TEG; Solar panels; Energy storage; Batteries; Energy harvesting methods; Supercapacitors; IoT; RF energy harvesting; Low-power electronics